Analysing the Philosophical Ideas of Nel Noddings on Empathy and Care - Yadava, Shalini (JOURNAL OF INDIAN EDUCATION, 2018)
The relationship between the teachers and students for a longtime was always looked up to as one that is built and nurtured on elements of trust, love and care. But this unfortunately has gone amiss. This relationship has now succumbed to the onslaught of market-driven economy where education is a ‘good’ to be bought and teacher a mere vehicle to deliver these goods keeping the paying capacity of the client in mind. Therefore, ‘care’ as a lived value is not a priority. The usual malaise which plagues the system is the focus on examinations and marks and not on the learning outcomes. When learning outcomes are the least of your concerns then the collateral damage is the absence of empathy and care in students. This paper is an attempt to provide insights into the strategies and activities which may be used with students in order to inculcate these values looking at the rich repertoire of ideas put forth by Nel Noddings who happens to be an authority on the subject.